Sustainable technologies, mega-events, and environmental awareness—Lessons from Expo 2020 Dubai - Al-Shihabi, Sameh; Aydin, Ridvan; Hadj-Alouane, Atidel; Alshanasi, Arwa (Frontiers in Sustainable Cities, 2023)
Different sustainable technologies were used in Expo 2020 Dubai to construct the different participating pavilions. Moreover, participating countries in the Expo have presented their state-of-the-art sustainable urban planning, transportation, and energy technologies. The purpose of using and presenting these technologies was to raise the visitors' environmental awareness. Thus, this study first presents a sample of sustainable technologies that were used or presented at the Expo. It then seeks to determine if using and presenting these technologies has fulfilled the Expo goal of raising its visitors' environmental awareness. It also tries to find out which environmental dimension was raised the most. For this purpose, a questionnaire was used to measure environmental awareness before and after visiting Expo 2020 Dubai. Statistically analyzing the responses of 1,108 frequent visitors shows that Expo 2020 Dubai achieved its goal of increasing visitors' environmental awareness, particularly the environmental attitude dimension. The findings also reveal that it is essential to have a point of interest devoted to environmental issues in similar events. This positive impact on the visitors should convince upcoming mega-event planners to follow Expo 2020 Dubai's steps. However, researchers need to develop strategies to raise the willingness to act dimension of environmental awareness.